Pengaruh Literasi Keuangan dan Pendidikan Kewirausahaan Terhadap Minat Berwirausaha Mahasiswa di Surabaya - Khoirunnisa; R Audi Cahya Luky; M. Saifur; Lailia (PUTRA JAWA PUBLISHER, 2025)
This study aims to examine the influence of financial literacy and entrepreneurship education on students' entrepreneurial intention. The research is motivated by the growing importance of enhancing human resource quality in the field of entrepreneurship through both financial understanding and relevant educational experiences. A quantitative approach was employed using multiple linear regression analysis. Data were collected through questionnaires distributed to 102 student respondents who expressed an interest in entrepreneurship. The results show that financial literacy has a significant effect on entrepreneurial intention, and entrepreneurship education also has a significant influence. Simultaneously, both independent variables significantly affect students’ entrepreneurial intention. This study emphasizes the importance of integrating financial literacy and entrepreneurship education in university entrepreneurship development programs to foster students' motivation and preparedness to become young entrepreneurs.